Three-Stage Transitional Theory: Egalitarian Gender Attitudes and Housework Share in 24 Countries - Kan, Man-Yee; Kolpashnikova, Kamila (Frontiers in Sociology, 2021)
How does the association between gender attitudes and housework share vary across countries and time? We examine the second demographic transition as it unmasks in the association between gender attitudes and housework participation. Using data of the 2002 and 2012 International Social Survey Programme (ISSP) for 24 countries, we find that the association between gender attitudes and housework share became stronger over time in most countries, signifying that the second demographic transition was in place. The results also show that the association varied across the 24 countries, reaching an equilibrium in many but at different stages. Our findings suggest that equilibria in the domestic division of labour take various forms and paces in the ISSP countries.